Ag NPs modified plasmonic Z-scheme photocatalyst Bi4Ti3O12/Ag/Ag3PO4 with improved performance for pollutants removal under visible light irradiation. Issue 10 (July 2020) - Lin, Chuanwei; Ma, Jianqing; Yi, Futao; Zhang, Huining; Qian, Yongxing; Zhang, Kefeng
Abstract: In a typical Z-scheme photocatalytic system, the visible light responsive component typically plays a crucial role and is often confined to materials sensitive to visible light. In addition, metallic nanodots or quantum dots are used as effective cocatalysts in the construction of plasmonic Z-scheme photocatalysts because of their strong light harvesting capacities under visible light illumination. In the present study, Bi4 Ti3 O12 nanosheets dominated with (001) crystal planes were successfully prepared via a facile molten-salt method, and BTO/Ag/APO composite samples were prepared by a simple precipitation method followed by photoreduction. The obtained BTO/Ag/APO composite exhibits improved photocatalytic activity for the decontamination of two typical organic pollutants, compared to bare Bi4 Ti3 O12 and Ag3 PO4 . Based on various characterization techniques, a Z-scheme electron transfer mechanism induced by the plasmonic effect was hypothesized to clarify the enhanced catalytic performances in this system. On the other hand, the LSPR effect of deposited silver nanoparticles can boost the molecular oxygen activation process and generate more superoxide radicals. This study provides a promising approach to apply highly effective photocatalytic degradation for environmental remediation.